Knockdown of circ-TTBK2 Inhibits Glioma Progression by Regulating miR-1283 and CHD1 - Han, Chengchen (Cancer Manag Res, 2020)
BACKGROUND: Dysregulated circular RNAs (circRNAs) are involved in the development of glioma. This paper aims to analyze the role and mechanism of circRNA tau tubulin kinase 2 (circ-TTBK2) in glioma progression. METHODS: The glioma samples and normal brain tissues were collected. The levels of circ-TTBK2, microRNA-1283 (miR-1283) and chromodomain helicase DNA-binding protein 1 (CHD1) were examined via quantitative reverse transcription polymerase chain reaction or Western blot. Cell proliferation, migration, invasion and glycolysis were determined via 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2-H-tetrazolium bromide, transwell assay, Western blot, glucose and lactate assay kits. The target relationship was analyzed via dual-luciferase reporter assay. The xenograft model was established using U251 cells. RESULTS: circ-TTBK2 expression was increased in glioma tissues and cells. circ-TTBK2 knockdown suppressed glioma cell proliferation, migration, invasion and glycolysis. circ-TTBK2 was a sponge for miR-1283, and knockdown of miR-1283 reversed the effect of circ-TTBK2 silence on glioma progression. CHD1 was targeted via miR-1283, and miR-1283 repressed glioma cell proliferation, migration, invasion and glycolysis via decreasing CHD1. Knockdown of circ-TTBK2-reduced CHD1 expression by mediating miR-1283. Silence of circ-TTBK2 reduced xenograft tumor growth. CONCLUSION: Down-regulation of circ-TTBK2 suppressed glioma development by regulating miR-1283 and CHD1, providing a new mechanism for understanding glioma pathogenesis.